The river we remember : a novel [compact disc, unabridged] - Krueger, William Kent (Simon & Schuster Audio, 2023)
On Memorial Day, as the people of Jewel, Minnesota gather to remember and honor the sacrifice of so many sons in the wars of the past, the half-clothed body of wealthy landowner Jimmy Quinn is found floating in the Alabaster River, dead from a shotgun blast. Investigation of the murder falls to Sheriff Brody Dern, a highly decorated war hero who still carries the physical and emotional scars from his military service. Even before Dern has the results of the autopsy, vicious rumors begin to circulate that the killer must be Noah Bluestone, a Native American WWII veteran who has recently returned to Jewel with a Japanese wife. As suspicions and accusations mount and the town teeters on the edge of more violence, Dern struggles not only to find the truth of Quinn's murder but also put to rest the demons from his own past. Caught up in the torrent of anger that sweeps through Jewel are a war widow and her adolescent son, the intrepid publisher of the local newspaper, an aging deputy, and a crusading female lawyer, all of whom struggle with their own tragic histories and harbor secrets that Quinn's death threatens to expose.